2013
DOI: 10.1097/mca.0b013e32835b0bdf
|View full text |Cite
|
Sign up to set email alerts
|

Increased red blood cell deformability and decreased aggregation as potential adaptive mechanisms in the slow coronary flow phenomenon

Abstract: The SCFP is associated with increased RBC deformability and decreased RBC aggregation. These hemorheological alterations, possibly also contributing factors in limiting the pathogenesis, can especially serve as beneficial adaptive mechanisms in the SCFP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…In large vessels blood flow is mainly determined by hematocrit, and it decreases inversely with the vessel diameter causing blood viscosity to remain steady 13). Because, increased blood viscosity results in slowing down the blood flow stasis,21) it has been hypothesized that to sustain normal blood stream within the arterial system, blood viscosity must decrease, and erythrocyte deformability must increase 22). Therefore, in addition to RBC deformability, WBV takes an active role in the perfusion of the capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…In large vessels blood flow is mainly determined by hematocrit, and it decreases inversely with the vessel diameter causing blood viscosity to remain steady 13). Because, increased blood viscosity results in slowing down the blood flow stasis,21) it has been hypothesized that to sustain normal blood stream within the arterial system, blood viscosity must decrease, and erythrocyte deformability must increase 22). Therefore, in addition to RBC deformability, WBV takes an active role in the perfusion of the capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…The enhanced RBC aggregation after stent implantation may contribute to impaired microvascular perfusion. In postmortem analysis of myocardium from patients with pronounced forms of slow‐flow and in a porcine model of ischemia/reperfusion in the no‐reflow area, RBC aggregates have been reported to obstruct capillaries …”
Section: Discussionmentioning
confidence: 99%
“…Hyperviscosity is assumed to be a pathological factor in impaired exchange between tissues and blood. Several studies reported that an elevated hematocrit leads to increased aggregation of red blood cells (RBCs) and increased blood viscosity, which might lead to decreased perfusion in tissues [4,5,22,24,30]. In one echocardiographic study, an increased hematocrit in healthy individuals was shown to reduce the coronary flow reserve [25].…”
Section: Discussionmentioning
confidence: 99%